Does extracorporeal membrane oxygenation attenuate hypoxic pulmonary vasoconstriction in a porcine model of global alveolar hypoxia?. Issue 7 (14th April 2020) - Holzgraefe, Bernhard; Larsson, Anders; Eksborg, Staffan; Kalzén, Håkan
Abstract : Background: During severe respiratory failure, hypoxic pulmonary vasoconstriction (HPV) is partly suppressed, but may still play a role in increasing pulmonary vascular resistance (PVR). Experimental studies suggest that the degree of HPV during severe respiratory failure is dependent on pulmonary oxygen tension (PvO2 ). Therefore, it has been suggested that increasing PvO2 by veno‐venous extracorporeal membrane oxygenation (V‐V ECMO) would adequately reduce PVR in V‐V ECMO patients. Objective: Whether increased PvO2 by V‐V ECMO decreases PVR in global alveolar hypoxia. Methods: Nine landrace pigs were ventilated with a mixture of oxygen and nitrogen. After 15 minutes of stable ventilation and hemodynamics, the animals were cannulated for V‐V ECMO. Starting with alveolar normoxia, the fraction of inspiratory oxygen (FI O2 ) was stepwise reduced to establish different degrees of alveolar hypoxia. PvO2 was increased by V‐V ECMO. Results: V‐V ECMO decreased PVR (from 5.5 [4.5‐7.1] to 3.4 [2.6‐3.9] mm Hg L −1  min, P  = .006) (median (interquartile range), ) during ventilation with FI O2 of 0.15. At lower FI O2, PVR increased; at FI O2 0.10 to 4.9 [4.2‐7.0], P  = .036, at FI O2 0.05 to 6.0 [4.3‐8.6], P  = .002, and at FI O2 0 to 5.4 [3.5 ‐ 7.0] mm Hg L −1  min, P  = .05. Conclusions: The effect of increased PvO2 by V‐V ECMO on PVR depended highly on the degree of alveolar hypoxia. Our results partly explain why V‐V ECMO does not always reduce right ventricular afterload at severe alveolar hypoxia.